MENCIPTAKAN MASJID SEBAGAI WADAH PEMBELAJARAN MASYARAKAT MELALUI LIBRARY LITERACY - Ellyana Ilsan Eka Putri (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2018)
To activate literasi on villages are still be the challenges, especiallyto access the information itself. It’s like Bejong which is located on the dale of the Raung mountain.In this digital era, this region is difficult to obtain access to information because the topography of Bejong region being hilly, so that the attempt to activate literasi be the challenge of which is more difficult. KKNPosdaya that based on mosque is trying to unlock the peoples insight one hamlet in the dale of the Raung mountain with education and social program that named library literacy.These activities are done both more or less 40 the day.The outcome of the activities shows to the establishment of the posdaya capable of being increase citizens participation in educational, religious and social activities.On top of that the initiation of the a mobile library and the inspiration library capable of being motivators and inspirators benefit the development of education activity, social and religiousness.